Changing the method of working with homeless people: a photovoice project in Italy. Issue 1 (2nd January 2018) - Gaboardi, Marta; Zuccalà, Giorgia; Lenzi, Michela; Ferrari, Sara; Santinello, Massimo
ABSTRACT: In Italy, many organizations are experimenting with the Housing First (HF) model to promote a change in how they work with homeless people. This change creates some difficulties, especially in promoting freedom of choice in people involved in the HF programs. This study explored the definition of "home" in homeless people's points of view. The study participants were 5 homeless men involved in a HF program called "The Road Home" implemented in the city of Padua. Data were collected using Photovoice, a photographic method based on participatory action research. During the project, the participants took photographs to illustrate their definitions of "home" and then engaged in a critical dialogue about the images represented in the photographs. The results of the study showed that occupants identified the home as being related to family, friendship, cohabitation, and hope for the future. The Photovoice project provided an opportunity to promote discussions that revealed the true needs of the people involved, and in the meantime, it brought a change to the program and to the community, in addition to promoting the HF model in the community.